ANFIS based sliding mode control of a DFIG wind turbine excited by an indirect matrix converter - Ahmad Khajeh; Hamed Torabi; Zahra Shabani Siahkaldeh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Doubly fed induction generator (DFIG) is very popular in commercial turbines installed worldwide. Indirect matrix converter (IMC) is a fully silicon-based converter without capacitor that could be used in wind turbines. In this paper a robust ANFIS based second order sliding mode controller is proposed to control the DFIG wind turbine excited by IMC converter. ANFIS is a combination of fuzzy logic control and artificial neural networks. This hybrid combination could decrease the complexity of the wind turbine system. This scheme does not need the exact mathematical model of the system as needed in classical control methods. The effectiveness of the proposed controller is verified by simulation results compared to the classical PI controller.